Dentist manpower development and geographical distribution of dentists in Taiwan - Feng-Chou Cheng; Julia Yu-Fong Chang; Tzu-Chiang Lin; Wen-Chiung Chang; Yung-Ta Chang; Chun-Pin Chiang (Elsevier, 2020)
Background/purpose: The development of dentists in Taiwan has been over a century. This study tried to explore the dentist manpower development and the current status of geographical distribution of dentists in Taiwan. Materials and methods: This study used the secondary data analysis to survey the changes of total dentist number from 1986 to 2018 and the geographic distribution of dentists in different levels of dental institutions in 2019. Results: The total number of dentists increased from 3739 in 1986 to 14,717 in 2018. The total number of hospital dentists increased from 809 in 1986 to 2121 in 2018. However, the proportion of hospital dentists in the total number of dentists decreased from 21.64% in 1986 to 14.41% in 2018. On the contrary, the total number of dental clinic dentists increased from 2930 in 1986 to 12,596 in 2018. The proportion of dental clinic dentists in the total number of dentists increased from 78.36% in 1986 to 85.59% in 2018. The northern region of Taiwan and Taipei City had 52.81% (7829/14,825) and 22.29% (3304/14,825) of the total number of dentists in 2019, respectively. Hospital dentists showed a significantly greater imbalance in geographic distribution than overall dentists. Conclusion: Our results indicate that Taiwan has the problems of oversupply of dentists and imbalance in geographical distribution of dentists. Because continuation of the current dentist manpower development may accelerate the oversupply and geographical imbalance of dentists, a mechanism for controlling the total dentist manpower should be implemented to prevent the deterioration of the problems.